2013
DOI: 10.1186/1471-2156-14-44
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide linkage analysis of congenital heart defects using MOD score analysis identifies two novel loci

Abstract: BackgroundCongenital heart defects (CHD) is the most common cause of death from a congenital structure abnormality in newborns and is often associated with fetal loss. There are many types of CHD. Human genetic studies have identified genes that are responsible for the inheritance of a particular type of CHD and for some types of CHD previously thought to be sporadic. However, occasionally different members of the same family might have anatomically distinct defects — for instance, one member with atrial septa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…SELS ( selenoprotein S , VIMP ) (*607918) gene was associated with a range of inflammatory markers, particularly in the context of cardiovascular disease (CVD) (Alanne et al, ; Cox et al, ). In addition to the previous results (Flaquer et al, ) attempted to identify the chromosomal regions that could be implicated in a possible common genetic framework shared by distinct types of CHD. He found two linkage regions, on chr15 and 18, and reported that SELS ( selenoprotein S ) , SNRPA1 ( small nuclear ribonucleoprotein polypeptide A1 ) (*603521), and PCSK6 (proprotein convertase subtilisin/kexin type 6 ) (*167405) as candidate genes on chr15 could be responsible for the development of different types of CHD (Flaquer et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SELS ( selenoprotein S , VIMP ) (*607918) gene was associated with a range of inflammatory markers, particularly in the context of cardiovascular disease (CVD) (Alanne et al, ; Cox et al, ). In addition to the previous results (Flaquer et al, ) attempted to identify the chromosomal regions that could be implicated in a possible common genetic framework shared by distinct types of CHD. He found two linkage regions, on chr15 and 18, and reported that SELS ( selenoprotein S ) , SNRPA1 ( small nuclear ribonucleoprotein polypeptide A1 ) (*603521), and PCSK6 (proprotein convertase subtilisin/kexin type 6 ) (*167405) as candidate genes on chr15 could be responsible for the development of different types of CHD (Flaquer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the previous results (Flaquer et al, ) attempted to identify the chromosomal regions that could be implicated in a possible common genetic framework shared by distinct types of CHD. He found two linkage regions, on chr15 and 18, and reported that SELS ( selenoprotein S ) , SNRPA1 ( small nuclear ribonucleoprotein polypeptide A1 ) (*603521), and PCSK6 (proprotein convertase subtilisin/kexin type 6 ) (*167405) as candidate genes on chr15 could be responsible for the development of different types of CHD (Flaquer et al, ). Our findings about the SELS , SNRPA1 , and PCSK6 genes confirm the previously reported results by (Alanne et al, ; Cox et al, ; Flaquer et al, )that these genes could be associated with the development of the ASD/VSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also reported that PCSK6 is of importance for the processing and activation of growth factors, primarily TGFB1 and PDGFB [22][23][24][25]. The influence of PCSK6 on the cardiovascular system and disease development still remains largely unknown, although variants in the PCSK6 genomic locus have been associated with congenital heart disease and aortic dissection [26,27] and PCSK6 has been implicated as a regulator of blood pressure in mice subjected to a sodium chloride enriched diet [28]. Utilizing a large human Biobank of Karolinska Endarterectomies, we have previously shown that upregulation of PCSK6 is associated with atherosclerotic plaque instability in patients with carotid stenosis [29].…”
Section: Introductionmentioning
confidence: 99%
“…Our group has implemented the MOD-score approach, including a routine to perform simulations under the null hypothesis, in the GENEHUNTER-MODSCORE (GHM) software [10][11][12][13] . Its application has led to the identification of a variety of genetic disease loci [14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%